Westminster Trades Council - Production Memorandum, 1 October 1942 (page 3) (1942)
1942 "Westminster Trades Council - Production Memorandum, 1 October 1942 (page 3)" [T0234c.jpg], 1942 Local trades councils were involved in a wide range of community issues during the war. This document deals with food distribution, shopping, part time employment children, nurseries, communal feeding, school meals, transport and entertainment.